Exploring the Plurality of Black Women's Gameplay Experiences - Rankin, Yolanda A.; Han, Na-eun (Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems, 2019)
Few gender-focused studies of video games explore the gameplay experiences of women of color, and those that do tend to only emphasize negative phenomena (i.e., racial or gender discrimination). In this paper, we conduct an exploratory case study attending to the motivations and gaming practices of Black college women. Questionnaire responses and focus group discussion illuminate the plurality of gameplay experiences for this specific population of Black college women. Sixty-five percent of this population enjoy the ubiquity of mobile games with casual and puzzle games being the most popular genres. However, academic responsibilities and competing recreational interests inhibit frequent gameplay. Consequently, this population of Black college women represent two types of casual gamers who report positive gameplay experiences, providing insights into creating a more inclusive gaming subculture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé